Effective health care for older people resident in care homes: the optimal study protocol for realist review - Goodman, Claire; Gordon, Adam L.; Martin, Finbarr; Davies, Sue L.; Iliffe, Steve; Bowman, Clive; Schneider, Justine; Meyer, Julienne; Victor, Christina; Gage, Heather; Gladman, John R.F.; Dening, Tom (Biomed Central, 2014)
Background Care homes in the UK rely on general practice for access to specialist medical and nursing care as well as referral to therapists and secondary care. Service delivery to care homes is highly variable in both quantity and quality. This variability is also evident in the commissioning and organisation of care home-specific services that range from the payment of incentives to general practitioners (GPs) to visit care homes, to the creation of care home specialist teams and outreach services run by geriatricians. No primary studies or systematic reviews have robustly evaluated the impact of these different approaches on organisation and resident-level outcomes. Our aim is to identify factors which may explain the perceived or demonstrated effectiveness of programmes to improve health-related outcomes in older people living in care homes.